High Security Ubiquitous H-Iot Monitoring System Based on a Wban - Kaschel-Carcamo, H (IEEE, 2021)
Wireless Body Area Networks (WBANs) based on the Internet of Things (IoT) play an important role in modern medical systems to monitor and supervise the health of a patient. WBANs have the ability to collect information on the physiological variables of the human body from patients in real time using smart sensors and then send the collected information remotely to a ubiquitous and highly secure H-IoT monitoring system to perform monitoring early detection of the patient s disease. The advantages of H-IoT are numerous and can greatly ease the burden on public health institutions and reduce a country s healthcare costs. In this paper we present the concepts of electronic health records and internet of medical things (HIoT) and the requirements needed to design a highly secure ubiquitous H-IoT monitoring system based on a WBAN.